Do Students' Perception of Lecturers' Pedagogical Competence Have an Effect on the Satisfaction of Islamic Religious Education Program Students? - Handrea Kurniawan; Eko Sujadi; Muhd. Odha Meditamar (Universitas Muhammadiyah Mataram, 2024)
Learning satisfaction is a crucial element that students must achieve, as it significantly affects the success of the learning process. This study aims to analyze the effect of students' perceptions of lecturers' pedagogic competence on their learning satisfaction. An online survey research design was employed. Over approximately two months, 154 students from the Islamic Education Study Program at a higher education institution in Jambi Province participated, completing scales measuring perceptions of lecturers' pedagogic competence and learning satisfaction. Data analysis in this study utilized descriptive statistics and simple linear regression. The findings indicate high student perceptions of lecturers' pedagogic competence and learning satisfaction. Regression analysis confirms a significant positive effect of students' perceptions of lecturers' pedagogic competence on learning satisfaction. If students perceive that the lecturer possesses good teaching abilities, can communicate the material clearly, and responds to students' learning needs, then it is highly likely that students will be satisfied with the learning process. This research has important implications for improving the quality of higher education learning. Lecturers should plan and design effective learning experiences, including selecting materials, teaching methods, and appropriate resources. Furthermore, the ability to utilize technology in teaching is increasingly important in today's digital era.